Review of exponential rise in domestic violence amid COVID-19: theories and perspectives - Rakubu, Kholofelo A; Olofinbiyi, Sogo Angel (ScienceRise: Juridical Science, 2022)
The need for continuous research on domestic violence could be more espoused by the exponential increase in domestic violence, such that characterized the global reign of corona virus. Domestic violence cases have been on the rise in South Africa since 1994; and despite the existence of legal protections and statutory instruments that attempt to hinder domestic violence, there continues to be prevalence of violent behaviours across different families. Indisputably, the outbreak of coronavirus has created myriads of consequences for justice system in South Africa and the world at large. Due to the outbreak, the South African government announced a lockdown to mitigate the spread of the virus. Nonetheless, within a span of one week of the lockdown, the South African Police Services (SAPS) reported a shocking rise in the number of gender-based violence cases, which was approximately reported as 89000. The lockdown primarily suggests that victims be locked with the perpetrators for a period until it is deemed safe to end the lockdown. Using a systematic review of the empirical literature, the paper provides a quadripartite criminological perspective (comprising differential association theory, classical theory, frustration-aggression theory and social bond theory) on the rise of domestic violence during the outbreak of the virus. It further explores the aftermaths of COVID-19 on criminal justice system in terms of dealing with diverse cases of domestic violence in the Republic. Factors pertaining to issues of access to justice system during the lockdown, poor police response and victim reporting, sense of helplessness by victims, delayed justice, as well as victim support, system are significantly evaluated